Effect of Slope and Varus Correction High Tibial Osteotomy in the ACL-Deficient and ACL-Reconstructed Knee on Kinematics and ACL Graft Force: A Biomechanical Analysis. Issue 2 (February 2021) - Imhoff, Florian B.; Comer, Brendan; Obopilwe, Elifho; Beitzel, Knut; Arciero, Robert A.; Mehl, Julian T.
Background: Correction of high posterior tibial slope is an important treatment option for revision of anterior cruciate ligament (ACL) failure as seen in clinical and biomechanical studies. In cases with moderate to severe medial compartment arthritis, an additional varus correction osteotomy may be added to improve alignment. Purpose: To investigate the influence of coronal and sagittal correction high tibial osteotomy in ACL-deficient and ACL-reconstructed knees on knee kinematics and ACL graft load. Study Design: Controlled laboratory study. Methods: Ten cadaveric knees were selected according to previous computed tomography measurements with increased native slope and slight varus tibial alignment (mean ± SD): slope, 9.9°± 1.4°; medial proximal tibia angle, 86.5°± 2.1°; age, 47.7 ± 5.8 years. A 10° anterior closing-wedge osteotomy, as well as an additional 5° of simulated varus correction osteotomy, were created and fixed using an external fixator. Four alignment conditions—native, varus correction, slope correction, and combined varus and slope correction—were randomly tested in 2 states: ACL-deficient and ACL-reconstructed. Compressive axial loads were applied to the tibia while mounted on a free-moving X-Y table and free-rotating tibia in a knee testing fixture. Three-dimensional motion tracking captured anterior tibial translation (ATT) and internal tibial rotation. Change of tensile forces on the reconstructed ACL graft were recorded. Results: In the ACL-deficient knee, an isolated varus correction led to a significant increase of ATT by 4.3 ± 4.0 mm ( P = .04). Isolated slope reduction resulted in the greatest decrease of ATT by 6.2 ± 4.3 mm ( P < .001). In the ACL-reconstructed knee, ATT showed comparable changes, while combined varus and slope correction led to lower ATT by 3.7 ± 2.6 mm ( P = .01) than ATT in the native alignment. Internal tibial rotation was not significantly altered by varus correction but significantly increased after isolated slope correction by 4.0°± 4.1° ( P < .01). Each isolated or combined osteotomy showed decreased forces on the graft as compared with the native state. The combined varus and slope osteotomy led to a mean decrease of ACL graft force by 33% at 200 N and by 58% at 400 N as compared with the native condition ( P < .001). Conclusion: A combined varus and slope correction led to a relevant decrease of ATT in the ACL-deficient and ACL-reconstructed cadaveric knee. ACL graft forces were significantly decreased after combined varus and slope correction. Thus, our biomechanical findings support the treatment goal of a perpendicular-aligned tibial plateau for ACL insufficiencies, especially in cases of revision surgery. Clinical Relevance: This study shows the beneficial knee kinematics and reduced forces on the ACL graft after combined varus and slope correction.